Pancreatic Injury after COVID-19 Vaccine—A Case Report - Artur Cieślewicz; Magdalena Dudek; Iwona Krela-Kaźmierczak; Anna Jabłecka; Maciej Lesiak; Katarzyna Korzeniowska (Vaccines, 2021)
The COVID-19 pandemic has caused more than 3 million deaths worldwide. Recently developed genetically engineered vaccines are the most critical solution for controlling the pandemic. Clinical trials on a large number of participants confirmed their safety and efficacy. However, with the growing number of vaccinated people, new infrequent adverse effects have been reported, not described in the medicinal product characteristics. We would like to report a case of acute pancreatic injury that occurred shortly after administering Pfizer BioNTech COVID-19 mRNA vaccine (Comirnaty). The report points out the potential need for close monitoring of patients reporting abdominal pain after vaccination (unresponsive to standard oral painkillers) because such symptom can be associated with acute pancreatitis.